Efficacy of Serum Cystatin C as a Diagnostic Marker of Early Renal Dysfunction in Hypertensive Individuals - Shakila, Saima; Farhad, MD Monaim; Hasan, Farhana; Sharmin, Shaila; Alam Bhuiyan, MD Monzurul; Sultana, Tuhin; Akanda, MD Iltutmish (Medicine Today, 2025)
Introduction: The aim of the present study was to find out the efficacy of serum Cystatin C as a diagnostic marker of early renal dysfunction in hypertensive individuals. Materials and Methods: This cross-sectional study was conducted from March 2022 to February 2023 in the Departments of Laboratory Medicine & Internal Medicine, BSMMU. All adult individuals (>18 years) attending OPD of Internal Medicine Department were enrolled in this study who fulfilling the inclusion and exclusion criteria. Then, 5 ml of venous blood was collected for the estimation of serum Cystatin C and serum creatinine. Five ml urine was collected for the estimation of spot urinary microalbumin. After data collection and processing, all statistical analysis was done by SPSS software windows version 26. Result: Total of 103 respondents from OPD of Internal Medicine was enrolled in this study. The mean age of the study population was 53.0±11.0 years. The male: female ratio is 2:1. The diagnostic performance of serum Cystatin C based on urinary microalbumin as the gold standard determining the best cut-off of 1.17 mg/L at an optimum sensitivity of 93.8% and specificity of 97.7%, PPV 88.2%, NPV 98.8% and accuracy 97.1%. The diagnostic performance of serum creatinine based on urinary microalbumin as the gold standard determining the best cut-off of 1.20 mg/L at an optimum sensitivity of 81.3%, specificity 98.9%, PPV 92.9%, NPV 96.6% and accuracy 96.1%. Conclusion: Serum Cystatin C level had significantly more correlation with microalbuminuria in hypertensive individuals. The area under the curve had shown that serum Cystatin C had an excellent discriminative ability to detect early renal dysfunction in hypertensive individuals. Medicine Today 2025, Vol.37 (1): 19-22